temples XXI - Grigoryeva, Elena (project baikal, 2014)
People have always built temples. Their diversity is infinite. Majestic cathedrals and mosques made of eternal stones neighbor a cardboard cathedral built by Pritzker laureate Shigeru Ban after the earthquake in New Zealand. Avantgarde experiments of new religions emerging in front of our eyes and no less surprising experiences of Catholic temples are side by side with an age-long strong tradition of Orthodox churches.After seventy years of gap thousands of temples of different confessions have been built and restored in the post-Soviet area. This issue includes projects of new religious buildings in Buryatia and Zabaikalie, Irkutsk and Angarsk, Krasnoyarsk, Kuzbass and Altai.The rise of construction of temples raises a lot of questions. Debates on a new appearance of churches develop simultaneously with discussions on the necessity of a new translation of the Bible into the modern language. The Union of Architects of Russia with the support of the Moscow Patriarchate of the Russian Orthodox Church launched a competition inviting ideas for a modern image of an Orthodox temple. The dogmata are unchanged, but the canons can be changed in time, as clergy members say. But how deep can such changes be? In what direction should the temple architecture develop? What is the best way for it to meet the challenges of our time, the changing lifestyle, the new rhythms and means of world perception?Again we fill our journal with questions to think them over together with our clever and nonindifferent reader.